2004
DOI: 10.1023/b:ddas.0000030084.01927.a8
|View full text |Cite
|
Sign up to set email alerts
|

Diminished Retention of Food in the Proximal Stomach Correlates with Increased Acidic Reflux in Patients with Gastroesophageal Reflux Disease and Dyspeptic Symptoms

Abstract: This work aimed at evaluating the intragastric distribution of food in patients with GERD and dyspepsia and its relationship to acidic reflux episodes. Gastric emptying and food retention in the proximal stomach were evaluated by scintigraphy in 12 healthy subjects and 19 patients with GERD and dyspepsia after a liquid test meal. Patients also underwent 24-hr esophageal pH monitoring, which included a 2-hr postprandial period following a similar test meal. Total gastric emptying was similar in patients and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
3
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 36 publications
4
40
3
2
Order By: Relevance
“…This autonomic improvement may act not only in the EGJ but also in the stomach to reduce tLESR. Disturbed postprandial meal distribution in the stomach is associated with increased tLESR in children fed with high volume and osmolality meal (25), and GERD patients have reduced proximal stomach meal retention (12). It is possible that autonomic function improvement in GERD would counteract motor derangements like the last one.…”
Section: Discussionmentioning
confidence: 99%
“…This autonomic improvement may act not only in the EGJ but also in the stomach to reduce tLESR. Disturbed postprandial meal distribution in the stomach is associated with increased tLESR in children fed with high volume and osmolality meal (25), and GERD patients have reduced proximal stomach meal retention (12). It is possible that autonomic function improvement in GERD would counteract motor derangements like the last one.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have also implicated delayed gastric emptying as a possible contributing factor which promotes acidic GER. 12,24 While PPIs such as omeprazole significantly decrease both gastric acid secretion and acid reflux, neither is completely inhibited by the PPI therapy and any delay in gastric emptying could still be a negative factor. In view of the very common use of PPIs to treat GERD symptoms, our results may also have important therapeutic implications for this patient group.…”
Section: -4mentioning
confidence: 99%
“…7,11 Exacerbation of this abnormality may possibly contribute to causing or worsening GER and increase the prevalence of dyspeptic symptoms commonly reported by this patient group. 7,[12][13][14] Drugs, which improve gastric emptying, can improve GERD symptoms, mucosal healing, and increase the efficacy of the antisecretory medications in chronic GERD management. 15,16 Tegaserod is a peripherally acting partial 5HT 4 -receptor agonist, which is approved for the treatment of women with irritable bowel syndrome with constipation (IBS-C) and for the treatment of men and women with chronic constipation.…”
Section: Introductionmentioning
confidence: 99%
“…In a study correlating gastric emptying and oesophageal pH impedance, Emerenziani et al [11] showed that the slower the emptying, the higher the pH and proximal extent of the refluxate. On the other hand, studies evaluating the intragastric distribution of food in patients with GOR disease and dyspepsia showed a significant negative correlation between the proximal gastric retention and the number of acidic reflux episodes, whereas total gastric emptying was similar in patients and controls [12]. In addition, the acquisition period is not well defined for the GOR studies, further complicating the interpretation.…”
Section: Discussionmentioning
confidence: 98%